Influences of sexual behaviors and vulnerability to HIV/AIDS among heterosexual ACB youth living in Windsor, Ontario. (November 2019) - Fante-Coleman, Tiyondah; Wilson, Ciann L.; Marcotte, Ashley Ann; McKie, Raymond; Travers, Robb; Furman, Ellis; ,
Little research has investigated relationships among heterosexual African, Caribbean, and Black (ACB) youth and the factors that influence their behavior and the behavioral expectations they have of their sexual partners. This study identifies influential factors of behavioral expectations, and how this behavior shapes vulnerability for human immunodeficiency virus. This article draws on data from the POWER project in Windsor, Canada. Six focus groups were held and attended by 26 ACB youth, and data were analyzed following thematic analysis guidelines. ACB youth adhered to gender roles prescribed through cultural heritage and religion. Gender inequality persists among young ACB youth, and sociopolitical history is hypothesized to shape normative gender roles, influencing relationship behaviors.